Konsep Orientasi Pasar dalam Perspektif Islam - Nurul Rizka Arumsari; Anindya Putri Utami; Budhi Cahyono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The concept of market orientation is an important cornerstone in modern marketing strategies, where companies not only focus on a deep understanding of customer needs, but also actively monitor competitors and maintain internal coordination between departments. Jaworski and Kohli (1993) emphasized that market orientation is one of the key factors that can affect a company's performance. Through the use of market information, companies can adjust their business strategies to meet current customer needs while anticipating future needs. A strong market orientation is believed to be able to make a significant contribution to increasing the company's competitiveness in the long term. However, if market orientation is based solely on materialistic goals and worldly gains, then the value of sustainability and societal well-being is often overlooked. From an Islamic perspective, market orientation needs to be based on sharia values, especially the principle of maslahah. This concept emphasizes that every business activity must bring benefits, avoid harm, and be in harmony with maqasid al-shariah, which is to protect religion, soul, intellect, descent, and property. Thus, market orientation is not only directed at the fulfillment of customer satisfaction and competitive advantage, but also at the achievement of blessings and social welfare. The integration of maslahah values in market orientation gives birth to the concept of Maslahah Market Responsiveness, which is the ability of companies to respond quickly and appropriately to market dynamics while still being based on ethics and social responsibility. This is an advantage in itself because it not only improves marketing performance, but also strengthens the company's image as a trustworthy and ethical entity. By combining conventional market orientation and sharia values, companies can build a sustainable competitive advantage, increase customer satisfaction, and make a positive contribution to society at large.